Information policy of Kazakhstan and media projection - Nurtazina, Р.А. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
The article presents the aspects of information policy in the mass media. The issues of media influence on the provision of information policy are considered. The concept of “information policy”, “information security” is highlighted, the implementation of state programs of Kazakhstan through the media is considered. The relevance of this strategy sets the task of the media to reflect the national interests and security of the society. Along with this, the formation of a common information and intellectual space, the interaction of different civilizations in the dialogue mode create favorable conditions for the development and targeted spread of national identity and spiritual and cultural content, which are reflected in the Head of State’s article “Seven Facets of the Great Steppe”.